Insect Pests of Stored Hazelnuts in Samsun Province, Turkey - Sullivan, Sebahat K. Ozman; Ocal, H.; Celik, N.; Sullivan, G.T. (International Society for Horticultural Science, 2009)
This study was conducted in 2007 on insect species associated with stored hazelnuts in the Samsun province of the Black Sea region of Turkey. Samples of shelled, in-shell and cracked hazelnuts were randomly collected and mixed at each processing plant. A sub-sample was taken from each plant and stored at 25°C and 60±5% RH in the laboratory. Samples were checked every two weeks and insects were identified and counted. Insects were found at all facilities. They were Plodia interpunctella (Hubner), Ephestia cautella (Walker), Tribolium confusum Jacquelin du Val, Tribolium castaneum (Herbst) and Oryzaephilus mercator (Fauvel). Ephestia cautella and T. confusum were the most common species. The parasitoid Bracon hebetor Say was also detected.
Keywords: Black Sea Region; Hazelnut Processing Plant; Parasitoid; Storage Pest